2019
DOI: 10.1080/1369118x.2019.1646777
|View full text |Cite
|
Sign up to set email alerts
|

Digital inequalities in the Internet of Things: differences in attitudes, material access, skills, and usage

Abstract: The Internet of Things (IoT) is more complex and abstract than previous information and communication technologies as there are many connections occurring. New challenges for users arise from increased amount of data, decisions made automatically, less visibility and more ambiguity, and magnified security and privacy risks. There is a fair chance that only a selective group will benefit, making it important to study IoT from a digital inequality perspective. The current study focused on health, home, and secur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 38 publications
0
41
0
3
Order By: Relevance
“…Under these circumstances, there is a risk that only a selective group will benefit from the advantages the digitalisation brings [12]. Additionally, there is another significant risk that refers to the problems related to privacy and security, which are growing [13].…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, there is a risk that only a selective group will benefit from the advantages the digitalisation brings [12]. Additionally, there is another significant risk that refers to the problems related to privacy and security, which are growing [13].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, tan solo han bastado treinta años para que 50.000 millones de dispositivos estén interconectados (Palfrey y Gasser, 2010). La inmersión tecnológica a escala global es, sin duda, una de las grandes evidencias de que la sociedad red es ya una realidad, por lo que si hace dos lustros la preocupación a escala global eran las brechas de acceso a tecnologías digitales, en la segunda década del siglo XXI la inquietud se centra en la brecha digital por uso eficiente de esa tecnología (Alva de la Rosa, 2015;Deursen, 2017;Deursen et al, 2019). El vertiginoso avance de la tecnología actual impone soluciones rápidas y adecuadas que doten a la población en general de respuestas formativas efectivas que le hagan estar preparada ante los retos de una nueva era marcada por la inteligencia artificial, el big data y el 5G (Aguaded, Marín-Gutiérrez y Caldeiro-Pedreira, 2018).…”
Section: Estado De La Cuestiónunclassified
“…Pese a las limitaciones del trabajo presentado, cuya metodología de muestreo es no probabilístico y, por tanto, no representativo del universo, supone un aporte empírico que evidencia que países con muy diferentes realidades en políticas e iniciativas tienen percepciones muy parecidas respecto al tema planteado y se sienten proactivos ante la problemática y el reto. El estudio supone un aporte más en la línea de investigaciones recientes (Blau y Shamir-Inbal, 2017;Deursen et al, 2019;Girón-Escudero;Cózar-Gutiérrez y González-Calero, 2019;Masanet, Guerrero-Pico y Establés, 2019) que dejan evidente el hecho de que la formación de las competencias digitales garantiza el acceso universal en igualdad de condiciones a las posibilidades que el siglo XXI nos brinda, y solo la concienciación a escala global, a gran escala y en todos los países conducirá a una verdadera disminución de las brechas digitales existentes.…”
Section: Conclusiones Y Discusiónunclassified
“…Research on internet skills has, for instance, long shown that education is an important resource for internet skills and that the older population has more problems using the internet [26,27]. These differences in skill levels are expected to be even more pronounced for the IoT because of its complexity and potential impact [28]. This is troublesome because people who rely the most on health-related services are likely to possess the lowest skill levels to use the health IoT for health support [2].…”
Section: Iot Skill Determinantsmentioning
confidence: 99%